2014
DOI: 10.1039/c4ra11411f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium nanoparticles supported on natural nanozeolite clinoptilolite as a catalyst for ligand and copper-free C–C and C–O cross coupling reactions in aqueous medium

Abstract: In this article, Pd 0 -nanoparticles supported on natural nanozeolite clinoptilolite (CP) were successfully synthesized, and the catalytic activity of the nanocatalyst was investigated in C-C and C-O coupling reactions, namely the Sonogashira and Ullmann condensation reactions in an aqueous medium. The nanocatalyst was characterized by various techniques such as powder-XRD, BET, SEM, TEM, HRTEM, TEM-EDS, ICP-OES and XPS. From an electron microscopy (SEM) study it can be inferred that the particles are mostly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 64 publications
1
8
0
Order By: Relevance
“…Their results showed that the specific surface of the natural nanozeolite (clinoptilolite) increased from 49.7 to 55.6 m 2 /g, and the pore diameter decreased from 12.19 to 8.05 nm, after acid activation. However, after the coupling of palladium in nanozeolite, the BET surface area decreased and the pore diameter tended to increase [33].…”
Section: Resultsmentioning
confidence: 99%
“…Their results showed that the specific surface of the natural nanozeolite (clinoptilolite) increased from 49.7 to 55.6 m 2 /g, and the pore diameter decreased from 12.19 to 8.05 nm, after acid activation. However, after the coupling of palladium in nanozeolite, the BET surface area decreased and the pore diameter tended to increase [33].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the reaction became sluggish when aryl bromides and chlorides were employed, being necessary longer reaction times. 69 …”
Section: Palladium Nanocatalystsmentioning
confidence: 99%
“…Palladium based systems include mainly the palladium complexes of phosphine ligands reported by the pioneers of C−O coupling reaction i. e. Buchwald and Hartwig . Some other important catalysts which have been reported recently include palladacycles of Schiff bases of ferrocene carboxaldehyde, supported palladium nanoparticles on nanozeolite clinoptilolite and graphene oxide . Palladium catalysts containing phosphine ligands suffer from disadvantage related to high sensitivity of phosphine ligands towards moisture and air.…”
Section: Introductionmentioning
confidence: 99%